2019
DOI: 10.1017/s0142716419000092
|View full text |Cite
|
Sign up to set email alerts
|

“It is alive!” Evidence for animacy effects in semantic categorization and lexical decision

Abstract: Animacy is one of the basic semantic features of word meaning and influences perceptual and episodic memory processes. However, evidence that this variable also influences lexicosemantic processing is mixed. As animacy is a semantic variable thought to have evolutionary roots, we first examined its influence in a semantic categorization task that did not make the animacy dimension salient, namely, concrete-abstract categorization. Animates were categorized faster (and more accurately) than inanimates. We then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 56 publications
1
7
0
5
Order By: Relevance
“…In our study, using animated animal stimuli may have facilitated the learning of individual conditions. Interestingly, a recent study showed that animacy facilitates semantic categorisation 50 , and this kind of interaction might explain why we observed a training effect only when animate stimuli and a semantic response domain were combined. The combination of these features in SS g+ may have enabled subjects to represent the different conditions more explicitly than in other versions of the valenced go/ no-go task.…”
Section: Discussionmentioning
confidence: 57%
“…In our study, using animated animal stimuli may have facilitated the learning of individual conditions. Interestingly, a recent study showed that animacy facilitates semantic categorisation 50 , and this kind of interaction might explain why we observed a training effect only when animate stimuli and a semantic response domain were combined. The combination of these features in SS g+ may have enabled subjects to represent the different conditions more explicitly than in other versions of the valenced go/ no-go task.…”
Section: Discussionmentioning
confidence: 57%
“…The results of Experiment 1 confirm the hypothesis derived from the richness-of-encoding account (Meinhardt et al, 2020 ) and the attentional account (Bugaiska et al, 2019 ) that animacy selectively enhances recollection. Even though animate words were encoded for a shorter period of time compared to inanimate words, animate words were more likely to be recollected than inanimate words (for a discussion of the relationship between response times and the richness of a word’s semantic representation, see Bonin et al, 2019 ). The animacy effect on the detection of new words was parallel to the animacy effect on the recollection of old words, as it should be (Glanzer & Adams, 1985 ).…”
Section: Methodsmentioning
confidence: 99%
“…La categorización es el proceso de distribución del objeto en una clase o categoría (Shadrikov, 2006). En el proceso de categorización, el conocimiento y las características semánticas son relevantes porque proporcionan una gran variedad de cualidades para el reconocimiento de palabras (Bonin et al, 2019).…”
Section: Semántica Del Lenguaje Y Categorizaciónunclassified